P14.20 Relationship myth between sex workers, sti's and hiv. (13th September 2015) - Joe, Q; Dee, A
Abstract : Introduction: For years Sex Workers in Australia, especially QLD, have been incorrectly attributed to the increase of STI's and HIV in the general community. This article will conclude that Sex Workers are not the cause of transmission increase in STI's and HIV. To the contrary Sex Workers have very low levels of STI's and HIV. Furthermore Sex Workers have helped to educated clients to reduce transmission of STI's and HIV. This article demonstrates the important role of Respect Inc in health promotion of Sex Workers with provision in education of STI's and HIV, so Sex Workers can keep themselves safe whilst doing Sex Work. Methods: The team will use a number of methods to collect data, all methods are traditional and dependent on targets. For example, we have used paper questionnaires to collect information from Sex Workers, this reduced barriers when asking Sex Workers personal questions. We conducted face to face interviews with some of the Sex Worker friendly GPs (General Practitioners) who provide sexual health certificates to Sex Workers. We have conducted telephone interviews with Sex Workers who do FIFO (fly in fly out) to regional mining towns in QLD. We collated this data with data provided by Respect Inc. Results: After collection of data we formatted charts and graphs. We found levels of STI's and HIV among Sex Workers were relatively low. GPs confirmed, Sex Workers are informed about STI's and HIV. Respect Inc provided data with hundreds of Sex Workers accessing offices across Qld for Safe Sex, STI's and HIV information, with positive sexual health outcomes. Conclusion: Sex Workers in Australia (QLD) have relatively low levels of STI's and HIV. Sex Workers are not the cause of increasing transmissions of STI's and HIV. Sex Workers often face stigma and discrimination in the wider community. Please respect Sex Work as a career of choice. SEX WORK IS REAL WORK